Exploring Future Pandemic Preparedness Through the Development of Preventive Vaccine Platforms and the Key Roles of International Organizations in a Global Health Crisis - Jihee Jeon; Eunyoung Kim (Vaccines)
Background: The emergence of more than 40 new infectious diseases since the 1980s has emerged as a serious global health concern, many of which are zoonotic. In response, many international organizations, including the US Centers for Disease Control and Prevention (CDC), the World Health Organization (WHO), and the European Center for Disease Prevention and Control (ECDC), have developed strategies to combat these health threats. The need for rapid vaccine development has been highlighted by Coronavirus disease 2019 (COVID-19), and mRNA technology has shown promise as a platform. While the acceleration of vaccine development has been successful, concerns have been raised about the technical limits, safety, supply, and distribution of vaccines. Objective: This study analyzes the status of vaccine platform development in global pandemics and explores ways to respond to future pandemic crises through an overview of the roles of international organizations and their support programs. It examines the key roles and partnerships of international organizations such as the World Health Organization (WHO), vaccine research and development expertise of the Coalition for Epidemic Preparedness Innovations (CEPI), control of the vaccine supply chain and distribution by the Global Alliance for Vaccines and Immunization (GAVI), and technology transfer capabilities of the International Vaccine Institute (IVI) in supporting the development, production, and supply of vaccine platform technologies for pandemic priority diseases announced by WHO and CEPI and analyzes their vaccine support programs and policies to identify effective ways to rapidly respond to future pandemics caused by emerging infectious diseases. Methods: This study focused on vaccine platform technology and the key roles of international organizations in the pandemic crisis. Literature data on vaccine platform development was collected, compared, and analyzed through national and international literature data search sites, referring to articles, journals, research reports, publications, books, guidelines, clinical trial data, and related reports. In addition, the websites of international vaccine support organizations, such as WHO, CEPI, GAVI, and IVI, were used to examine vaccine support projects, initiatives, and collaborations through literature reviews and case study methods. Results: The COVID-19 pandemic brought focus on the necessity for developing innovative vaccine platforms. Despite initial concerns, the swift integration of cutting-edge development technologies, mass production capabilities, and global collaboration have made messenger RNA (mRNA) vaccines a game-changing technology. As a result of the successful application of novel vaccine platforms, it is important to address the remaining challenges, including technical limits, safety concerns, and equitable global distribution. To achieve this, it is essential to review the regulatory, policy, and support initiatives that have been implemented in response to the COVID-19 pandemic, with particular emphasis on the key stages of vaccine development, production, and distribution, to prepare for future pandemics. An analysis of the status of vaccine development for priority pandemic diseases implies the need for balanced vaccine platform development. Also, international organizations such as WHO, CEPI, GAVI, and IVI play key roles in pandemic preparedness and the development and distribution of preventive vaccines. These organizations collaborated to improve accessibility to vaccines, strengthen the global response to infectious diseases, and address global health issues. The COVID-19 pandemic response demonstrates how the synergistic collaboration of WHO’s standardized guidelines, CEPI’s vaccine research and development expertise, GAVI’s control of the vaccine supply chain and distribution, and IVI’s technology transfer capabilities can be united to create a successful process for vaccine development and distribution. Conclusions: In preparation for future pandemics, a balanced vaccine platform development is essential. It should include a balanced investment in both novel technologies such as mRNA and viral vector-based vaccines and traditional platforms. The goal is to develop vaccine platform technologies that can be applied to emerging infectious diseases efficiently and increase manufacturing and distribution capabilities for future pandemics. Moreover, international vaccine support organizations should play key roles in setting the direction of global networking and preparing for international vaccine support programs to address the limitations of previous pandemic responses. As a result, by transforming future pandemic threats from unpredictable crises to surmountable challenges, it is expected to strengthen global health systems and reduce the social and economic burden of emerging infectious diseases in the long term.